Quantum correlations of identical particles subject to classical environmental noise - Beggi, Andrea; Buscemi, Fabrizio; Bordone, Paolo (Quantum information processing, 2016)
In this work, we propose a measure for the quantum discord of indistinguishable particles, based on the definition of entanglement of particles given in Wiseman and Vaccaro (Phys Rev Lett 91:097902, 2003 . doi: 10.1103/PhysRevLett.91.097902 ). This discord of particles is then used to evaluate the quantum correlations in a system of two identical bosons (fermions), where the particles perform a quantum random walk described by the Hubbard Hamiltonian in a 1D lattice. The dynamics of the particles is either unperturbed or subject to a classical environmental noise—such as random telegraph, pink or brown noise. The observed results are consistent with those for the entanglement of particles , and we observe that on-site interaction between particles have an important protective effect on correlations against the decoherence of the system.